2014
DOI: 10.1038/cddis.2014.270
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34a: a potential therapeutic target in human cancer

Abstract: MicroRNAs (miRs) are small noncoding RNAs that negatively regulate gene expression by binding to the three untranslated regions of their target mRNAs. Deregulations of miRs were shown to play pivotal roles in tumorigenesis and progression. Recent research efforts have been devoted to translating these basic discoveries into applications that could improve the therapeutic outcome of patients with cancer. MiR-34a is a highly conserved miR throughout many different species. In humans, there are three homologs (hs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
216
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(225 citation statements)
references
References 89 publications
(106 reference statements)
9
216
0
Order By: Relevance
“…The results were similar to observations in colon, breast and lung cancer, in which miR-34a expression was downregulated, and overexpression of miR-34a inhibited cell proliferation (7,26,27). The present study selected SIRT1, an energy sensor, to validate the antitumor mechanism of miR-34a in prostate cancer cells.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The results were similar to observations in colon, breast and lung cancer, in which miR-34a expression was downregulated, and overexpression of miR-34a inhibited cell proliferation (7,26,27). The present study selected SIRT1, an energy sensor, to validate the antitumor mechanism of miR-34a in prostate cancer cells.…”
Section: Discussionsupporting
confidence: 70%
“…These results indicated that dysregulation of miR-34a may be involved in the pathogenesis of human prostate cancer. miR-34a is located on chromosome 1p-36; deletion or loss of heterozygosity of this region is associated with a number of types of human tumor, including breast cancer, lung cancer and cervical cancer (7). In addition, miR-34a is the target gene of the p53 tumor suppressor gene, and p53 tumor suppressor gene mutation is involved in the development of prostate cancer (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The miR-34 family, including miR-34a, miR-34b and miR-34c, is directly regulated by p53 and has been reported to induce apoptosis and cell cycle arrest and, thus, act as a tumor suppressor in cancer cells (81). As was expected, low expression of miR-34a has also been found to be important in GBC (82).…”
Section: Tumor Suppressor Micrornassupporting
confidence: 54%
“…[35][36][37][38] Furthermore, it has been reported that miR-34 decreased the expression of Bcl-2, leading to an increase in apoptosis. 39 As one of the key regulators of apoptosis and autophagy, Bcl-2 protein possesses four conserved Bcl-2 homology domains (BH1-4) and can inhibit Beclin1-dependent autophagy by binding to Beclin1 under starvation conditions.…”
Section: Introductionmentioning
confidence: 99%